Robert v. Gustin, The Revised Municipal Code of East St. Louis of 1908, at 361, § 888 (1909) - (:unkn) unknown (My University, 1908)
Chapter 39-Misdemeanors, Article 1-Offenses Affecting the Public Peace and Quiet, § 888: Prohibited selling, loaning, furnishing, to any minor a gun, pistol, or other firearm. Violators fined not more than one hundred dollars for each offense.
Keywords: TRANSFER - MINORS